Correlation between Implant Geometry, Bone Density, and the Insertion Torque/Depth Integral: A Study on Bovine Ribs - Danilo Alessio Di Stefano; Paolo Arosio; Vittoria Perrotti; Giovanna Iezzi; Antonio Scarano; Adriano Piattelli (MDPI AG, 2019)
During insertion of dental implants, measurement of dynamic parameters such as the torque-depth curve integral or insertion energy might convey more information about primary stability than traditional static parameters such as the insertion or removal torque. However, the relationship between these dynamic parameters, bone density, and implant geometry is not well understood. The aim of this investigation was to compare static and dynamic implant stability measurements concerning three different implant designs when implants were inserted into bovine bone ribs and dynamic parameters were collected using an instantaneous torque measuring implant motor. Standard implant osteotomies were created in segments of bovine ribs. After measuring the bone density using the implant motor, 10 cylindrical, 10 hybrid tapered-cylindrical, and 10 modified cylindrical implants were placed, and their primary stability was assessed by measuring the torque–depth curve integral, along with insertion and removal torque. The relationship between these quantities, bone density, and implant geometry was investigated by means of regression and covariance analysis. The regression lines describing the relationship between the torque–depth integral and bone density differed significantly from those describing the relationship between insertion torque, removal torque, and bone density for all three designs. The torque–depth curve integral provides different information about immediate primary stability than insertion and removal torque and in certain clinical conditions might be more reliable than these static parameters for assessing implant primary stability. Further research should be carried out to investigate the findings of the present study.